MENINGKATKAN KEMAMPUAN MENGINGAT MELALUI PEMBERIAN LAYANAN PENGUASAAN KONTEN TEKNIK LOCIPADA SISWA KELAS X SMA NEGERI 6 MEDAN T.A 2014/2015 - Akbar, Imam Syuhada; Milfayeti, Milfayeti (JURNAL DIVERSITA, 2015)
The purpose of this study is to examine the effectiveness of the technique loci in improving memory in class X SMAN 6 Academic Year 2014/2015. The method used is action research counseling (PTBK). The population of this study were students of class X-3 SMA Negeri 6 Medan which numbered 40 people. Data analysis techniques in this study using descriptive qualitative data analysis techniques. Based on the results obtained before the service is 26% and is still in the category of "less" and is still in the analysis were not good, therefore it is necessary for the application of the use of techniques loci were done through the implementation of content services in order to resolve the problem remembering. After the use of techniques loci in remembering which is done through the implementation of content services using two cycles obtained results of the analysis has reached 87.50% and is in the category of "Good". So the hypothesis which states that "by using the loci technique can improve the ability to remember in class X SMAN 6 Academic Year 2014/2015 is implemented through the provision of content services" accepted.Keyword: Content Service, Memory, Loci technique